Seasonal changes in immune parameters of rainbow trout (Oncorhynchus mykiss), brook trout (Salvelinus fontinalis) and brook trout × Arctic charr hybrids (Salvelinus fontinalis × Salvelinus alpinus alpinus) - Papežíková, Ivana; Mareš, Jan; Vojtek, Libor; Hyršl, Pavel; Marková, Zdeňka; Šimková, Andrea; Bartoňková, Jana; Navrátil, Stanislav; Palíková, Miroslava (Fish & shellfish immunology, 2016)
Despite the high number of studies concerning seasonality of immune response in fish, information for some fish species is still scarce. Here, we assess seasonal changes in leukocyte counts and several immune parameters in three groups of farmed salmonids, i.e. brook trout (Salvelinus fontinalis), brook trout x Arctic charr hybrids (Salvelinus fontinalis x Salvelinus alpinus alpinus) and rainbow trout (Oncorhynchus mykiss) reared under the same conditions and fed with the same feed. Fish were sampled in five periods of the year (late April, early July, late August, early November and early February) and leukocyte counts, respiratory burst of blood phagocytes, lysozyme concentration in skin mucus and total complement activity were measured. Generalized linear models using fish body length as a continuous predictor and sampling period and fish species as categorical predictors, were significant for each of the parameters analysed. The highest seasonal variations in measured parameters were found in rainbow trout and lowest in hybrids. Our results confirm that measures of innate and adaptive immunity are strongly affected by season in all three groups of salmonids. The results will contribute to the improved assessment of immunocompetence in farmed fishes, essential for future sustainable development in aquaculture.
Keywords: Oncorhynchus mykiss; fagocyty; Respiratory Burst; Hybridization, Genetic; počet leukocytů; Trout; respirační vzplanutí; kůže; Leukocyte Count; pstruh; zvířata; hybridizace genetická; hlen; Phagocytes; komplement; roční období; Seasons; Muramidase; Mucus; Animals; Complement System Proteins; muramidasa; Skin